Competence building and leveraging in interorganizational relations - Martens, Rudy; Heene, Aimé; Sanchez, Ron (Advances in applied business strategy ;, 2008)
The competence-based perspective on strategy and management offers an integrative approach to strategy and management theory, research, and practice. Nearly two decades of research, theory development, and application have demonstrated the theoretical coherence, researchability, and practicability of a fundamental focus on organizational competences. The competence-based perspective is now providing a productive broad church for advancing theory development, research, and practice in both strategic and general management.In the twenty-first century, network-based strategies and processes are becoming essential aspects of both firm strategies and operations. We are therefore pleased to present here a new volume focusing on inter-organizational processes for competence building and competence leveraging.The papers in this volume begin with an in-depth literature review by Frederic Prevot of inter-organizational relations in alternative approaches to the creation and management of competences. The next three papers (by Joerg Freiling et al., Gabriel Gaullino and Frederic Prevot, and Heike Proff) elaborate several of these approaches to managing inter-organizational processes for competence building and competence reconstructionapplied in the contexts of the healthcare industry, educational programs, the utilities market, and processes of mergers and acquisitions.New ventures are also important forums for competence building in and among firms, and two papers (by Henri Burgers et al. and by Bhaskar Prasad and Rudy Martens) analyze the impact of corporate venturing on the competence modes that a firm adopts and the role of inter-organizational communication networks on technological innovation processes as an important form of competence building.The role of leadership in effective competence management is examined by Janice Black and Richard Oliver in a paper that identifies the differing leadership skills required in three different competence-building contexts: within a single organization, in a multi-foci organization, and within an industry.Finally, recognizing the difficulty that many firms have in identifying their competences, Graham Hubbard describes a practical approach to determining a firms current capabilities. Case-based analysis using Hubbards framework suggests that business units may actually have a rather small number (fewer than five) of identifiable and strategically significant capabilities that should play in central role in a firms competence-building processes.This volume is produced annually. It offers an integrative approach to strategy and management theory, research, and practice.